Dinamika Cyberbullying di Media Sosial dan Dampaknya Terhadap Kehidupan Sosial Remaja - Arifin, Ibrahim; Nirwana; Nurmagfira; Aksayanti (DISCOURSE: Indonesian Journal of Social Studies and Education, 2025)
The development of information and communication technology (ICT) has brought significant changes in social interactions, but it has also raised new challenges, one of which is cyberbullying. Cyberbullying is a form of bullying perpetrated through digital media with unique characteristics such as anonymity of the perpetrator, wide reach, and rapid spread of information, which makes it more difficult to control than conventional bullying. This study aims to explore the factors that contribute to cyberbullying behavior and its impact on adolescent mental health through a systematic review of the available literature. Using a qualitative approach based on a literature review, this study examines the social and psychological dynamics behind the phenomenon of cyberbullying as well as possible interventions. The results show that cyberbullying is influenced by individual, social and contextual factors, such as the aggressiveness of the perpetrator, social norms in the online environment, and lack of parental supervision. The impact is significant, including increased anxiety, depression and social isolation in victims. To address this problem, a comprehensive strategy is needed, including digital literacy education, strengthening anti-cyberbullying policies, and involving schools and parents in creating a safer digital environment. This study contributes to a deeper understanding of cyberbullying and mitigation measures that can be applied in the context of education and social policy. Further studies are needed to examine the effectiveness of long-term interventions and the role of social media platforms in preventing and addressing cyberbullying.